Functional recovery by colon organoid transplantation in a mouse model of radiation proctitis. (August 2021) - Jee, JooHyun; Park, Jun-Hyeok; Im, Jung Ho; Kim, Mi Sun; Park, Enoch; Lim, Taegyu; Choi, Woo Hee; Kim, Jee Hyun; Kim, Woo Ram; Ko, Ji Su; Jeong, Sang Yun; Ko, Seung Young; et al.
Abstract: Radiation proctitis is the collateral damage that occurs to healthy cells during radiation treatment of pelvic malignancies. Conservative treatment of radiation proctitis can mitigate inflammatory symptoms, but, to date, no therapeutic options are available for direct recovery of the damaged colonic epithelium. The present study assessed the ability of colon organoid-based regeneration to treat radiation proctitis. Radiation proctitis was induced in mice by irradiating their recta, followed by enema-based transplantation of mouse colon organoids. The transplanted colon organoids were found to successfully engraft onto the damaged rectal mucosa of the irradiated mice, reconstituting epithelial structure and integrity. Lgr5 + stem cells were shown to be pivotal to colon organoid mediated regeneration. Endoscopic examination showed the efficacy of localized transplantation of colon organoids with fibrin glue to irradiated sites. These findings provide useful insights into the use of colon organoid-based regenerative therapy for the treatment of radiation proctitis.